Path Analysis: Health Promotion Information Access of Parent Caretaking Pattern through Parenting Education - Tri Sunarsih; Bhisma Murti; Sapja Anantanyu; Mahendra Wijaya (International Journal of Evaluation and Research in Education (IJERE), 2016)
Parents often inhibit learning process organized by education, due to their ignorance about how to educate child well. Incapability of dealing with those changes leads to dysfunctional families, and problematic children. This research aimed: to analyzed the health promotion information access pattern of parent caretaking pattern through parenting education. This study was taken place in Karanganyar Regency area, Central Java. As a survey research with cross-sectional design, this study built on questionnaire as a main instrument of collecting primary data, while secondary data was obtained from recording in the related institutions in Karanganyar Regency. The sample consisted of 108 parents, taken using purposive sampling technique. To address the objective, multiple linear regression and path analyses were used. Its important finding was that interactions with other students’ parent, with other members of family, and with media simultaneously affected significantly the parenting pattern holistically, either directly or indirectly. The largest effect on parenting was exerted by interaction between parent and media. From those findings, the author recommended that the appropriate parenting education strategies were to provide adequate information such as reading books for parent, to facilitate parent discussion to generate interaction between parents so that they shared information more frequently.